COMMUNITY ASSISTANCE IN RECLAMATION AND RESTORATION EFFORTS OF COAL MINING ECOSYSTEMS IN SAWAHLUNTO CITY - Zulfa Zulfa; Elvawati Elvawati; Irwan Irwan; Yenita Yatim; Yudas Sabaggalet; Renita Renita; Fandi Firman; Yenni Melia (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2026)
Sawahlunto City has a long history as a coal mining center, but this activity has left ecological challenges in the form of critical land and mine voids. This community service program aims to increase local community awareness and skills in independent reclamation and ecosystem restoration. Methods used include environmental regulation awareness, training in pioneer vegetation planting techniques, and the utilization of post-mining land for productive sectors. The community service results show a 70% increase in partners' understanding of land restoration techniques and the formation of environmentally conscious community groups actively involved in reforestation of former mining areas.